Clinical–pathological characteristics and short-term follow-up associated with proliferation, apoptosis and angiogenesis in a prospective cohort of patients with colorectal tumours. Issue 4 (April 2019) - Redondo, Maximino; Abitei, Cristina; Téllez, Teresa; Fúnez, Rafael; Pereda, Teresa; Rodrigo, Isabel; Betancourt, Ana M; García-Aranda, Marilina; Rueda, Antonio; Martínez García, Rafael Cayetano; Morales Suarez-Varela, María Manuela; Zabalza, Iñaki; et al.
We investigate the clinical and pathological features related to variations in colorectal tumour apoptosis, proliferation and angiogenesis and the influence of the latter in short-term mortality (2 years); 551 tumour samples from a prospective cohort of patients with colorectal cancer were examined and tumour biology markers were determined as follows: percentage of apoptotic cells, by the terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling technique; Ki-67 antigen, as a cell proliferation marker and density of microvessels (as a marker of angiogenesis). An increase in the percentage of cellular apoptosis is significantly related to the presence of poorly differentiated tumours, with vascular invasion (p < 0.001). The CD105 angiogenesis marker is not related to any clinical–pathological parameter except that of higher frequency in older patients (p = 0.03). Ki-67 is more frequently expressed in tumours with less nervous invasion (p = 0.05). Neither apoptosis nor angiogenesis present any significant association with short-term survival. The only marker clearly related to 2-year survival is Ki-67, which is shown to be a good prognostic factor in the multivariate analysis (hazard ratio = 0.49; 95% confidence interval = 0.27–0.90). Therefore, in a prospective cohort of colorectal cancer patients, only Ki-67 is a marker of good prognosis in short-term follow-up.